Serological proteomic biomarkers to identify Paracoccidioides species and risk of relapse - Sylvestre, Tatiane Fernanda [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Da Silva, Julhiany de Fátima [UNESP]; Miranda Paniago, Anamaria Mello; Weber, Simone Schneider; Pauletti, Bianca Alves; Carvalho, Lídia Raquel de [UNESP]; Dos Santos, Lucilene Delazari [UNESP]; Mendes, Rinaldo Poncio [UNESP] (Public Library of Science (PLoS), 2018)
The sensitivity of the double agar gel immunodiffusion test is about 90% in patients with untreated paracoccidioidomycosis (PCM), but it is much lower in cases of relapse. In addition, serum from patients with PCM caused by Paracoccidioides lutzii, frequent in the Midwest region of Brazil, do not react with the classical antigen obtained from Pb B-339. These findings showed the need for alternative diagnostic methods, such as biological markers through proteomics. The aim of this study was to identify biomarkers for the safe identification of PCM relapse and specific proteins that could distinguish infections caused by Paracoccidioides brasiliensis from those produced by Paracoccidioides lutzii. Proteomic analysis was performed in serum from 9 patients with PCM caused by P. brasiliensis, with and without relapse, from 4 patients with PCM produced by P. lutzii, and from 3 healthy controls. The comparative evaluation of the 29 identified plasma proteins suggested that the presence of the immunoglobulin (Ig) alpha-2 chain C region and the absence of Ig heavy chain V-III TIL indicate infection by P. lutzii. In addition, the absence of complement factor B protein might be a predictor of relapse. The evaluation of these proteins in a higher number of patients should be carried out in order to validate these findings.